The Impact Of The To The Coastal Community In The Beach Of Cermin, Perbaungan SubDistrict, Serdang Bedagai District, Sumatra Utara Province - Dian Taruli Silitonga; Hamdi Hamid; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This Research  was conducted in Mei 2017 in the Beach Cermin, Perbaungan Sub-District, Serdang Bedagai District, North Sumatera Province. The method used in this research is survey method. The purpose of this research is to knowing the tourism activies to the coastal community economy and to know the impact of tourism activities to the coastal community social. Based on the results of research that has been conducted on the existing activities in Beach Cermin is the presence of toilet guards. For the activities in the economy is the coastal community mirrors provide leasing of facilities on the beach, such as game rental, swimming tire rental, and tent rental for a place to relax, and for activities in the existing social Beach Mirror is the appearance of art every Saturday.Keywords: impact, tourism, Serdang Bedagai district